Renovating material for bulged and warped ceramic tiles as well as preparation method and application of renovating material
By using the renovation materials made of alpine, titanium pink powder, talc powder, alkaline lime and other materials, combined with emulsion and acrylic resin and other ingredients to form a strong alkali environment and hydrolyze dichlorobine to generate hydrophilic membrane, solving the renovation of tiles in precipitation Or the problem of poor adhesion performance in the humid environment has significantly improved the bonding stability of tiles.
Patent Information
- Application Number
- CN202411470547.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-21
AI Technical Summary
In the prior art, ceramic tile renovation materials have poor adhesion performance when used in areas with high precipitation and coastal areas with heavy humidity, resulting in susceptibility to rainfall or reflux during drying and curing.
A renovation material including calcined kaolin, titanium dioxide, talc, soda lime, water, emulsion, acrylic resin, defoaming agent and dichlorobutane is used. The material is mixed by stirring the two components evenly to form a strong alkali environment and hydrolyzes dichlorobutane at high temperatures to form a hydrophobic film, enhancing adhesion properties.
The refurbished material forms a strong alkali environment in the hybrid system and releases heat. Hydrolyzed dichlorobine generates a hydrophobic membrane, which significantly improves the adhesion performance. Especially in the precipitation or humidity environment, it can effectively resist the impact of water and ensure the tiles of tiles. Stable bonding.
Smart Images

Figure BDA0005094571140000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a renovation material for bulging and warping tiles, and a preparation method and application thereof. Background Art
[0002] As people's living standards improve, the demand for home decoration is getting higher and higher. In decoration, floor tiles are one of the indispensable decorative materials. However, sometimes we will find that after using tiles for a period of time, the tiles will be arched.
[0003] There are usually the following reasons for the bulging and warping of tiles: 1. Thermal expansion and contraction of tiles: During long-term use, tiles will be affected by temperature and produce thermal expansion and contraction. If sufficient expansion gaps are not reserved when laying tiles, or the gaps are blocked by fillers, the tiles cannot release stress when expanding, which will cause arching. 2. Improper construction: During construction, if the ratio of cement to yellow sand is incorrect, such as low cement grade and too much yellow sand, the cement layer will not have enough adhesion, which will cause the tiles to warp. 3. Improper ground foundation treatment, such as the ground is too smooth and not roughened, will also affect the adhesion between the tiles and the cement layer. 4. Improper material selection or use: The quality of the tile glue used is not up to standard, or after the tiles are laid, if they are not fully dried and cured before being put into use, especially walking on them or placing heavy objects on them, it will cause the tiles and the cement layer to delaminate, and then warp. 5. Environmental factors: Seasonal changes, large indoor temperature differences and other factors will also cause thermal expansion and contraction of tiles. If the gaps between the tiles are not reserved enough, arching is likely to occur.
[0004] At present, the treatment method for bulging and warping of ceramic tiles is usually to cut out the ceramic tiles along the joint edges, then remove the old adhesive (cement) in the cut area of the ground, lay the renovation materials on the ground substrate, and then stick the ceramic tiles (coated with water-based adhesive) back to the original position to complete the repair. Before re-laying the ceramic tiles, the key step is to treat the base layer with a ceramic tile renovation interface agent. Existing interface agents usually take some time to dry and solidify after being applied to the base layer, and the general drying and curing time is 12-24 hours. However, in some areas with heavy precipitation and coastal areas with heavy humidity, during the ceramic tile renovation process, after the interface agent is applied, during the drying and curing process, if there is rainy weather or humid weather, water will come into contact with the interface agent, which can easily affect the adhesion performance of the interface agent. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problem that the renovation material (interface agent) in the prior art has poor adhesion performance when used in areas with heavy precipitation and coastal areas with heavy humidity, and to provide a renovation material for preventing ceramic tiles from bulging and warping, and a preparation method and application thereof.
[0006] In order to solve the above-mentioned technical problems, the technical solution adopted by the present invention is:
[0007] A renovation material for bulging and warping tiles, comprising a first component and a second component to be mixed;
[0008] Wherein, the first component comprises, by weight:
[0009] 10-25 parts by weight of calcined kaolin;
[0010] 5-10 parts by weight of titanium dioxide;
[0011] 5-15 parts by weight of talc;
[0012] 5-15 parts by weight of soda lime;
[0013] Wherein, the second component comprises by weight:
[0014] Water 5-15 parts by weight;
[0015] Emulsion 15-25 parts by weight;
[0016] 0.5-1.5 parts by weight of acrylic resin;
[0017] Defoaming agent 0.1-0.5 parts by weight;
[0018] 4-10 parts by weight of dichlorobutane.
[0019] As a further optimization of the renovation material for bulging and warping tiles of the present invention: the emulsion is a styrene acrylic emulsion.
[0020] As a further optimization of the renovation material for bulging and warping tiles of the present invention: the acrylic resin is a thermoplastic acrylic resin.
[0021] As a further optimization of the renovation material for bulging and warping tiles of the present invention: the defoaming agent is a silicone defoaming agent or a polyether defoaming agent.
[0022] As a further optimization of the renovation material for bulging and warping tiles of the present invention: the calcined kaolin is calcined kaolin passing through an 800-1200 mesh sieve, and the titanium dioxide is rutile titanium dioxide.
[0023] The present invention also provides a method for preparing the above-mentioned renovation material, comprising the following steps:
[0024] S1, mixing calcined kaolin, titanium dioxide, talc and soda lime and stirring evenly to obtain a first component;
[0025] S2, mixing water, emulsion, acrylic resin, dichlorobutane and defoamer and stirring evenly to obtain a second component;
[0026] S3. Seal the first component and the second component separately. When using, mix the first component and the second component and stir them evenly to obtain the renovation material.
[0027] The stirring conditions in step S1 are: stirring at a speed of 500-600 r / min for 0.5-1 h, the stirring conditions in step S2 are: stirring at a speed of 2000-3000 r / min for 1-2 h, and the stirring conditions in step S3 are: stirring at a speed of 1500-2000 r / min for 0.5-1 h.
[0028] The present invention also provides an application of the above-mentioned renovation material in the renovation construction of bulging and warping tiles. The renovation construction method is specifically: cutting out the warped tiles along the splicing edges, applying the renovation material on the floor or wall area corresponding to the cut tiles and drying and forming them, applying water-based adhesive on the back of the tiles, and then paving the tiles back to their original positions.
[0029] The invention has the following beneficial effects: the renovation material of the invention is divided into two components, wherein the first component contains soda lime, which is mainly composed of calcium oxide, sodium hydroxide and potassium hydroxide. When the first component is mixed with the second component, the calcium oxide in the soda lime can react with water to generate calcium hydroxide, which is conducive to forming a strong alkaline environment. At the same time, the reaction is an exothermic reaction, and heat is released during the reaction process. In the mixed system, dichlorobutane is hydrolyzed under alkaline conditions and high temperature conditions to form a large amount of free butanol, and the free butanol is attached to a fixed surface to form a hydrophobic film, thereby playing a role in strengthening the hydrophobicity of particles in the system and enhancing the resistance to water. DETAILED DESCRIPTION
[0030] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the content of the present invention is not limited to the following embodiments.
[0031] <Refurbishment Materials>
[0032] It includes a first component and a second component to be mixed;
[0033] The first component includes, by weight:
[0034] 10-25 parts by weight of calcined kaolin, the particle size of the calcined kaolin is 800-1200 meshes.
[0035] 5-10 parts by weight of titanium dioxide, which is rutile titanium dioxide.
[0036] 5-15 parts by weight of talc;
[0037] 5-15 parts by weight of soda lime;
[0038] Wherein, the second component comprises by weight:
[0039] Water 5-15 parts by weight;
[0040] 15-25 parts by weight of the emulsion, which is a styrene acrylic emulsion.
[0041] 0.5-1.5 parts by weight of acrylic resin, wherein the acrylic resin is a thermoplastic acrylic resin.
[0042] The defoaming agent is 0.1-0.5 parts by weight, and the defoaming agent is a silicone defoaming agent or a polyether defoaming agent.
[0043] 4-10 parts by weight of dichlorobutane.
[0044] <Method for preparing renovation material>
[0045] The following steps are involved:
[0046] S1, mixing calcined kaolin, titanium dioxide, talc and soda lime and stirring evenly to obtain a first component;
[0047] The stirring conditions are: stirring at a speed of 500-600 r / min for 0.5-1 h;
[0048] S2, mixing water, emulsion, acrylic resin, dichlorobutane and defoamer and stirring evenly to obtain a second component;
[0049] The stirring conditions are: stirring at a speed of 2000-3000 r / min for 1-2 h;
[0050] S3. Seal the first component and the second component separately. When using, mix the first component and the second component and stir them evenly to obtain the renovation material.
[0051] The stirring conditions are: stirring at a speed of 1500-2000r / min for 0.5-1h.
[0052] <Application of renovation materials>
[0053] The renovation construction method is as follows: cut the warped tiles along the joint edge, apply the renovation material to the floor or wall area corresponding to the cut tiles and dry them, apply water-based adhesive on the back of the tiles, and then lay the tiles back to their original positions.
[0054] <Example 1>
[0055] Take 200 g of calcined kaolin passed through a 1000 mesh sieve, 60 g of rutile titanium dioxide, 100 g of talc, and 100 g of soda lime, mix them and stir them evenly to obtain a first component.
[0056] Take 200 g of styrene-acrylic emulsion (BASF water-based styrene-acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 100 g of water, 10 g of acrylic resin (Japan Mitsubishi BR-116), 3 g of silicone defoamer (BYK-065), and 50 g of dichlorobutane, mix and stir evenly to obtain the second component.
[0057] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0058] <Example 2>
[0059] Take 250 g of calcined kaolin passed through an 800-mesh sieve, 50 g of rutile titanium dioxide, 150 g of talc, and 50 g of soda lime, mix them and stir them evenly to obtain a first component.
[0060] Take 250 g (BASF water-based styrene acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 50 g water, 15 g acrylic resin (Japan Mitsubishi BR-116), 1 g polyether defoamer (polyglycerol ether), and 100 g dichlorobutane, mix and stir evenly to obtain the second component.
[0061] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0062] <Example 3>
[0063] Take 100 g of calcined kaolin passed through a 1200 mesh sieve, 100 g of rutile titanium dioxide, 50 g of talc, and 150 g of soda lime, mix them and stir them evenly to obtain a first component.
[0064] Take 150 g of styrene-acrylic emulsion (BASF water-based styrene-acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 150 g of water, 5 g of acrylic resin (Japan Mitsubishi BR-116), 5 g of silicone defoamer (KMT-2024), and 40 g of dichlorobutane, mix and stir evenly to obtain the second component.
[0065] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0066] <Example 4>
[0067] Take 120 g of calcined kaolin passed through a 900-mesh sieve, 60 g of rutile titanium dioxide, 80 g of talc, and 120 g of soda lime, mix them and stir them evenly to obtain a first component.
[0068] Take 185 g of styrene-acrylic emulsion (BASF water-based styrene-acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 75 g of water, 12 g of acrylic resin (Japan Mitsubishi BR-116), 3 g of silicone defoaming agent (AFE-1247), and 60 g of dichlorobutane, mix and stir evenly to obtain the second component.
[0069] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0070] <Example 5>
[0071] Take 220 g of calcined kaolin passed through a 90-mesh sieve, 650 g of rutile titanium dioxide, 110 g of talc, and 85 g of soda lime, mix them and stir them evenly to obtain a first component.
[0072] Take 210 g of styrene acrylic emulsion (BASF water-based styrene acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 65 g of water, 6 g of acrylic resin (Japan Mitsubishi BR-116), 4 g of silicone defoaming agent (BYK-065), and 55 g of dichlorobutane, mix and stir evenly to obtain the second component.
[0073] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0074] <Example 6>
[0075] Take 180 g of calcined kaolin passed through a 1100 mesh sieve, 75 g of rutile titanium dioxide, 75 g of talc, and 120 g of soda lime, mix them and stir them evenly to obtain a first component.
[0076] Take 185 g of styrene-acrylic emulsion (BASF water-based styrene-acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 95 g of water, 7 g of acrylic resin (Japan Mitsubishi BR-116), 2.5 g of silicone defoamer (BYK-065), and 55 g of dichlorobutane, mix and stir evenly to obtain the second component.
[0077] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0078] <Comparative Example 1>
[0079] Take 200 g of calcined kaolin passed through a 1000 mesh sieve, 60 g of rutile titanium dioxide and 100 g of talc, mix and stir evenly to obtain a first component.
[0080] Take 200 g of styrene acrylic emulsion (BASF water-based styrene acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 100 g of water, 10 g of polyacrylate ammonium salt acrylic resin and 3 g of silicone defoamer (BYK-065), mix and stir evenly to obtain the second component.
[0081] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0082] <Comparative Example 2>
[0083] 200 g of calcined kaolin passed through a 1000 mesh sieve, 60 g of rutile titanium dioxide, and 100 g of talc were mixed and stirred evenly to obtain a first component.
[0084] Take 200 g of styrene acrylic emulsion (BASF water-based styrene acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 100 g of water, 10 g of polyacrylate ammonium salt acrylic resin, 3 g of silicone defoamer (BYK-065), and 50 g of dichlorobutane, mix and stir evenly to obtain the second component.
[0085] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0086] <Comparative Example 3>
[0087] Take 200 g of calcined kaolin passed through a 1000 mesh sieve, 60 g of rutile titanium dioxide, 100 g of talc, and 100 g of soda lime, mix them and stir them evenly to obtain a first component.
[0088] Take 200 g of styrene acrylic emulsion (BASF water-based styrene acrylic emulsion 5041, active ingredient content 53%, curing conditions: room temperature curing), 100 g of water, 10 g of polyacrylate ammonium salt acrylic resin, and 3 g of silicone defoamer (BYK-065), mix and stir evenly to obtain the second component.
[0089] The first component and the second component are sealed separately. When in use, the first component and the second component are mixed and stirred evenly to obtain the renovation material.
[0090] <Water resistance>
[0091] The water resistance of the renovation materials prepared in Example <1-6> and Comparative Example <1-3> was tested. The testing method was carried out according to the method in JGJ110-2008, specifically:
[0092] Remove the lifted tiles, and then apply the mixed renovation materials on the concrete substrate. Spray the coating layer with water 6h, 8h, 10h and 12h after coating, with a water spraying amount of 1.5g / cm 2 , 24 hours after coating, apply water-based adhesive on the back of the ultra-thin tile, and then lay the ultra-thin tile on the coated surface of the concrete and press hard. After 10 hours, bond the standard block to the tile, and use a through-type jack to test the bonding force of the tile. The specific performance test results are shown in Table 1 below.
[0093] Table 1: Performance Test
[0094]
[0095] It can be seen from the above table that after the water-repellent component is added, the bonding strength of the samples in Example <1-6> under the four test scenarios of 6h water spraying, 8h water spraying, 10h water spraying and 12h water spraying is higher than that of Comparative Example <1-3>. <1> Compared with the comparative example <1-3>, the bonding strength is quite different. In the test scenario of 12h water spraying, the bonding strength of the embodiment <1-3> is <1> Compared with the comparative example <1-3>, the difference in bonding strength is small. The inventor believes that this is because the renovation material is nearly dry after 12 hours, and the effect of water spraying on its bonding performance is small. The bonding strength of each comparative example in comparative example <1-3> and embodiment <1-6> in each test scenario is not much different. This is because the water-resistant components in the two components complement each other and are indispensable.
[0096] The construction method of renovating tiles using the renovation material of the present invention can also be: cutting out the warped tiles along the splicing edges or using suction cups to vertically take out the loose tiles, coating the renovation material on the back of the tiles and then paving the tiles back to their original positions, with a coating thickness of 1-2 mm.
[0097] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A renovation material for bulging and warping tiles, characterized in that: The renovation material includes a first component and a second component to be mixed; Wherein, the first component comprises, by weight: 10-25 parts by weight of calcined kaolin; 5-10 parts by weight of titanium dioxide; 5-15 parts by weight of talc; 5-15 parts by weight of soda lime; Wherein, the second component comprises by weight: Water 5-15 parts by weight; Emulsion 15-25 parts by weight; 0.5-1.5 parts by weight of acrylic resin; Defoaming agent 0.1-0.5 parts by weight; 4-10 parts by weight of dichlorobutane.
2. A renovation material for bulging and warping tiles as claimed in claim 1, characterized in that: The emulsion is a styrene acrylic emulsion.
3. A renovation material for bulging and warping tiles as claimed in claim 1, characterized in that: The acrylic resin is a thermoplastic acrylic resin.
4. A renovation material for bulging and warping tiles as claimed in claim 1, characterized in that: The defoamer is a silicone defoamer or a polyether defoamer.
5. A renovation material for bulging and warping tiles as claimed in claim 1, characterized in that: The calcined kaolin is calcined kaolin that has passed through a 800-1200 mesh sieve, and the titanium dioxide is rutile titanium dioxide.
6. The method for preparing the renovation material according to claim 1, characterized in that: The following steps are involved: S1, mixing calcined kaolin, titanium dioxide, talc and soda lime and stirring evenly to obtain a first component; S2, mixing water, acrylic resin, emulsion, acrylic resin, dichlorobutane and defoamer and stirring evenly to obtain a second component; S3. Seal the first component and the second component separately. When using, mix the first component and the second component and stir them evenly to obtain the renovation material.
7. The method for preparing the renovation material according to claim 6, characterized in that: The stirring conditions in step S1 are: stirring at a speed of 500-600 r / min for 0.5-1 h, the stirring conditions in step S2 are: stirring at a speed of 2000-3000 r / min for 1-2 h, and the stirring conditions in step S3 are: stirring at a speed of 1500-2000 r / min for 0.5-1 h.
8. Use of the material as claimed in claim 1 in the renovation of bulging and warping tiles.
9. The use according to claim 8, characterized in that: The specific renovation construction method is: cut out the warped tiles along the joint edges, apply the renovation material on the floor or wall area corresponding to the cut tiles and dry them into shape, apply water-based adhesive on the back of the tiles, and then lay the tiles back to their original positions.
Citation Information
Patent Citations
Novel environment-friendly method for refurbishing old ceramic tiles
CN101891503A
Polymeric sand-fixing waterproof material and preparation method thereof
CN110229566A
Multifunctional wall leveling and renewing material
CN110713363A
Composite primer applied to old ceramic tile exterior wall renovation, preparation method and construction method
CN113652127A